1st Evidence-based Italian Consensus Conference on Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy for Peritoneal Carcinosis from Ovarian Cancer. Issue 6 (November 2017) - Cavaliere, Davide; Cirocchi, Roberto; Coccolini, Federico; Fagotti, Anna; Fambrini, Massimiliano; Federici, Orietta; Lorusso, Domenica; Vaira, Marco; Ceresoli, Marco; Delrio, Paolo; Garofalo, Alfredo; Pignata, Sandro; et al.
Ovarian cancer (OC) remains relatively rare, although it is among the top 4 causes of cancer death for women younger than 50. The aggressive nature of the disease and its often late diagnosis with peritoneal involvement have an impact on prognosis. The current scientific literature presents ambiguous or uncertain indications for management of peritoneal carcinosis (PC) from OC, both owing to the lack of sufficient scientific data and their heterogeneity or lack of consistency. Therefore, the Italian Society of Surgical Oncology (SICO), the Italian Society of Obstetrics and Gynaecology, the Italian Association of Hospital Obstetricians and Gynaecologists, and the Italian Association of Medical Oncology conducted a multidisciplinary consensus conference (CC) on management of advanced OC presenting with PC during the SICO annual meeting in Naples, Italy, on September 10-11, 2015. An expert committee developed questions on diagnosis and staging work-up, indications, and procedural aspects for peritonectomy, systemic chemotherapy, and hyperthermic intraperitoneal chemotherapy for PC from OC. These questions were provided to 6 invited speakers who answered with an evidence-based report. Each report was submitted to a jury panel, representative of Italian experts in the fields of surgical oncology, gynecology, and medical oncology. The jury panel revised the reports before and after the open discussion during the CC. This article is the final document containing the clinical evidence reports and statements, revised and approved by all the authors before submission.